2018
DOI: 10.1136/bmj.k1551
|View full text |Cite|
|
Sign up to set email alerts
|

Vertebroplasty versus sham procedure for painful acute osteoporotic vertebral compression fractures (VERTOS IV): randomised sham controlled clinical trial

Abstract: ObjectiveTo assess whether percutaneous vertebroplasty results in more pain relief than a sham procedure in patients with acute osteoporotic compression fractures of the vertebral body.DesignRandomised, double blind, sham controlled clinical trial.SettingFour community hospitals in the Netherlands, 2011-15.Participants180 participants requiring treatment for acute osteoporotic vertebral compression fractures were randomised to either vertebroplasty (n=91) or a sham procedure (n=89).InterventionsParticipants re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
177
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(181 citation statements)
references
References 24 publications
3
177
0
1
Order By: Relevance
“…Two of the three recent trials observed no clinically important benefits of vertebroplasty over placebo at any time point . While the third trial reported a benefit favouring vertebroplasty for their primary outcome, the proportion of participants achieving an overall pain score of less than 4 at 14 days, differences between groups using the metric of comparison of mean improvement in pain, was smaller than what is generally accepted as clinically relevant at all time points up to 6 months other than 3 days .…”
Section: Three Additional Trials Fail To Overturn Conclusion From Thmentioning
confidence: 86%
See 2 more Smart Citations
“…Two of the three recent trials observed no clinically important benefits of vertebroplasty over placebo at any time point . While the third trial reported a benefit favouring vertebroplasty for their primary outcome, the proportion of participants achieving an overall pain score of less than 4 at 14 days, differences between groups using the metric of comparison of mean improvement in pain, was smaller than what is generally accepted as clinically relevant at all time points up to 6 months other than 3 days .…”
Section: Three Additional Trials Fail To Overturn Conclusion From Thmentioning
confidence: 86%
“…Two of the three recent trials observed no clinically important benefits of vertebroplasty over placebo at any time point. 20,22 While the third trial reported a benefit favouring vertebroplasty for their primary outcome, the proportion of participants achieving an overall pain score of less than 4 at 14 days, differences between groups using the metric of comparison of mean improvement in pain, was smaller than what is generally accepted as clinically relevant at all time points up to 6 months other than 3 days. 21 In addition, there were possible sources of bias including use of a potentially less credible placebo in comparison to previous trials (which may have led to the significant difference in proportion of participants who correctly guessed their treatment allocation at 14 days), and selective reporting of pre-specified outcomes (including failing to report success of blinding at 3 days), that may have led to an overestimation of benefit compared to other placebo-controlled trials.…”
Section: Three Additional Trials Fail To Overturn Conclusion From Thmentioning
confidence: 98%
See 1 more Smart Citation
“…VERTOS IV is the most recent double-blinded shamcontrolled RCT to evaluate the safety and efficacy of vertebroplasty in VCFs (n = 180). 15 Patients were recruited via written questionnaires from referrals for spinal radiographs rather than referrals for vertebroplasty. Median duration of back pain prior to vertebroplasty was 6.1 weeks (IQR 4.1-8.7).…”
Section: Blinded Randomised Controlled Trialsmentioning
confidence: 99%
“…Fragility fractures cause deformity as well as pain and seem to be associated with an increased mortality from respiratory disease 8. Importantly, no long term trials have evaluated whether vertebroplasty performed at any stage improves long term outcomes such as deformity and mortality when combined with medical treatment of osteoporosis.…”
mentioning
confidence: 99%